2. Work in Progress: From Phocis to Aetolia: Ethnicity and Federalism in Greek Antiquity (PhD Dissertation) - Husøy, Thomas Alexander (Teiresias Journal Online, 2023)
https://doi.org/10.23889/SUthesis.62811